The Characterization of Bimodal Droplet Size Distributions in the Ultrafiltration of Highly Concentrated Emulsions Applied to the Production of Biodiesel - Falahati, Hamid (University of Ottawa (Canada), 2010)
A non-reactive model system comprising a highly concentrated and unstable oil-in-water emulsion was used to investigate the retention of oil by the membrane in producing biodiesel with a membrane reactor. Critical flux was identified using the relationship between the permeate flux and transmembrane pressure along with the separation efficiency of the membrane. It was shown that separation efficiencies above 99.5% could be obtained at all operating conditions up to the critical flux. The critical flux obtained in the model oil-water system ranged between 30 and 40 L/m2/h for a cross flow velocity of 0.8 m/s. According to ASTM D6751 and EN 14214, the unreacted oil concentration in the biodiesel should not exceed 0.2 wt% (2000 ppm). It was observed that the concentration of oil in all collected permeate samples using the oil-water system was below 0.2 wt% (2000 ppm) when operating at a flux below the critical flux. Studies to date have been limited to the characterization of low concentrated emulsions below 15 vol.%. The average oil droplet size in highly concentrated emulsions was measured as 3200 nm employing direct light scattering (DLS) measurement methods. Cake layer thickness was calculated based on a droplet size of 3200 nm for the various oil concentrations. It was observed that the estimated cake layer thickness of 20 to 80 mm, was larger than external diameter of the membrane tube i.e. 6 mm. Settling of the concentrated emulsion permitted the detection of a smaller particle size distribution (30-100 nm) within the larger particles averaging 3200 nm. It was identified that DLS methods could not efficiently give the droplet size distribution of the oil in the emulsion since large particles interfered with the detection of smaller particles. The content of the smaller particles represented 1% of the total weight of oil at 30°C and 5% at 70°C. This was too low to be detected using DLS measurements but was sufficient to affect ultrafiltration. In order to study the critical flux in the presence of transesterification reaction and the effect of cross flow velocity on separation, various oils were transesterified in another membrane reactor providing higher cross flow velocity of 1.8 m/s. The oils tested were canola, corn, sunflower and unrefined soy oils (Free Fatty Acids (FFA< 1%)), and waste cooking oil (FFA= 9%). The quality of all biodiesel samples was studied in terms of glycerine, mono-glyceride (MG), di-glyceride (DG) and tri-glyceride (TG) concentrations. The composition of all biodiesel samples were in the range required by ASTM D6751 and EN 14214 standards. Therefore the critical flux, based on composition was determined to be above 70 L/m2/h for a cross flow velocity of 1.8 m/s. For canola oil, higher cross flow velocity provides better separation by reducing materials deposition on the surface of the membrane due to higher shearing. A critical flux based on operating pressure in the reactor was reached for waste cooking and pre-treated corn oils. This flux ranged from 30 to 40 L/m 2/h. This is in a pretty good agreement with the non-reactive model system employed in this study. It was identified that the reaction residence time in the reactor was an extremely important design parameter affecting the operating pressure in the reactor. Lower residence times increased the amount of unreacted oil inside the reactor which caused an increase in pressure within the reactor. All FAME samples were water washed only once to remove free glycerine and residues. The glycerine concentration for these samples was very low after this single wash. In conventional reactors a number of water washing stages are required to remove all finely suspended hydrophilic materials from the biodiesel and reduce the glycerine content to below 0.02 wt% (200 ppm) as required by ASTM and EN standards. Since the membrane reactor integrates reaction and separation simultaneously, the permeate was ultrafiltered and free of hydrophilic colloidal matters e.g. cell debris. Previous work showed that the membrane reactor requires less catalyst than conventional reactors. The amount of catalyst required for the treatment of waste oil was optimized. This results in a neutral pH of the FAME phase (pH=7). The lower catalyst requirement combined with the decreased need for wash waters leads to a more environmentally friendly process. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.